Level of independence, functional capacity and respiratory muscle strength of patients with mucopolysaccharidosis type VI in the Northeast of Brazil - Figueirêdo,Bárbara Bernardo Rinaldo da Silva (2018)
Abstract Objectives: to assess the functional independence, functional capacity and respiratory muscle strength (RMS) in individuals with mucopolysaccharidosis (MPS) type VI. Methods: in this cross-sectional study, the Pediatric Evaluation of Disability Inventory (PEDI) and the Functional Independence Measure (FIM) scales were used to assess the functional independence. The functional capacity and the RMS were assessed by a 6-minute walk test (6MWT) and Manovacuometry, respectively. The associations between RMS and 6MWD were analyzed by using the adjusted simple linear regression models. And besides, the T-test was used to compare the differences among the groups. Results: twenty-four patients with MPS VI were included, the median age was 8 (ranged from 2-38 years old). The PEDI presented a functional performance below the expectations at the self-care and mobility domains of 33.3% when compared to groups of Brazilian children at the same age assessed with typical development. The decreased social function was found in only one single case. According to the FIM, of the 12 patients evaluated (age> 7.5 years), 58.3% were classified as modified dependence and 41.7% as modified independence. The mean distance in the 6MWT was significantly lower than predicted, 263m in G1 (children, n= 7) and 336m in G2 (adolescents and adults, n=6), p<0.001. The RMS was also lower than predicted in both groups, except for the RMS in G1. Conclusions: the functional capacity and the RMS were significantly reduced in individuals with MPS VI, with a decreased functional independence in one-third of the patients. However, a multidisciplinary follow-up in this population is essential to prevent, diagnose and treat early complications.